ANALISIS TEORI BEHAVIORISME (THORNDIKE) PADA PELAJARAN MATEMATIKA DAN BAHASA INDONESIA SDN UPT XVII MUKTI JAYA ACEH SINGKIL - Nur Rohman (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2021)
This study aims to describe (1) how the application of Thorndike's learning theory inlearning (2) Thorndike's learning theory in learning Mathematics and Indonesian atSDN UPT XVII Mukti Jaya Singkohor District, Aceh Singkil Regency. This researchuses qualitative research. In the form of this research to describe and analyzephenomena, events, social activities, beliefs, and thoughts of a person individually or ingroups. This type of research is a case study research with data collection techniquesused include observation, interviews and documentation. The results of this studyindicate that Thorndike's theory is one part of the behaviorism theory developed byEdward Lee Thorndike in Williamsburg. In the elaboration of the theory, it is dividedinto several parts, namely: first, the first stage of thought which includes: the law ofreadiness, the law of practice, the law of consequences and the law of attitude. Second,the second stage of thought is a form of revision carried out by Thorndike regarding thelaw of practice and the law of effect. Based on the analysis of existing data, it can beseen that Thorndike's learning theory has indirectly been applied by teachers, especiallyin mathematics and Indonesian lessons. This can be seen from the compatibility betweenThorndike's learning theory and the stages used by the teacher in carrying out theteaching and learning process in the classroom.